Teacher Interaction Analysis by Using Initiation, Response and Feedback (IRF) - Ahadya Rahmania (Journal of English Language Teaching and Islamic Integration, 2025)
This study examines how the IRF model and teacher feedback strategies influence student participation in an Indonesian elementary school classroom. By analyzing teacher-student interactions, it aims to highlight the balance between structured instruction and student autonomy in foreign language learning. A summary of a review of foreign language learning for elementary school students regarding recognizing the names of fruits and constructing sentences with the names of these fruits is a good start to learning a foreign language, where students are given a lot of vocabulary as initial capital for them to compose sentences and speak, while the role of the teacher Here, apart from being a material provider, the teacher also becomes a judge who is able to reflect on what students do and provide feedback that builds students to learn English better.